(3jfHhY GdMjGI (B((3JaSjQ GdbQBf GdYXje(B)s - (3MLI GdOjf CHh YHO Gddg eMeO Hf YHO Gddg Hf XaQ GdUbdj Gdecj, GHf XaQ,J (B565 (3g` s
(3ChdgG (B:s
(3jHOC ai CKfGA JaSjQ ShQI GdaGJMI hChdg(B: (3GdeYGaQi hCNHQfi Cfg bQCg hSeYg HbQAJg Ydi GdTjN GdRGgO CHj HcQ eMeO Hf GdhdjO TjNi GdePchQ hQhGg Yfg GdGSJGP GdePchQ BfkaG, Ke bGd di CNHQfi CHh YHO Gddg s
(3BNQgG (B:s
(3Je GdLRA GdKGfi ef cJGH jfHhY GdMjGI, jJdhg ai GdLRA GdKGdK Ef TGA Gddg JYGdi GdcdGe Ydi bhdg JYGdi (B((3hGdPjf EPG aYdhG aGMTI(B) (3Edi bhdg SHMGfg(B: ((3hSfLRi GdTGcQjf(Bq) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2052s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJaSjQ hYdhe GdbQBfs